« Territoire zéro chômeur de longue durée » : les luttes d’interprétation d’un droit à l’emploi - Mathieu Béraud; Jean-Pascal Higelé (La Nouvelle Revue du Travail)
The “zero long-term unemployed territory” experiment relies on the idea that the resources dedicated to long-term unemployment (benefits, job-search support, etc.) can be redeployed to create new jobs. The project is also based on the idea that it is not the lack of employability of the unemployed, but the “employer-ability” of companies, i.e. the ability of companies to become employers, that is the cause of unemployment. The experiment therefore provides for the creation of ad hoc employers – so-called employment-oriented companies – to hire all willing long-term unemployed of the experimental territory. The project is therefore experimenting a form of right to employment with blurred boundaries. Based on a survey of one of the ten experimental territories, the article analyses observed disputes as to the interpretation of the right to employment as a right to an employer or as a right to wage work. It more broadly questions the forms of labour institutions.